2018
DOI: 10.1007/s10029-018-1776-2
|View full text |Cite
|
Sign up to set email alerts
|

Decreased re-operation rate for recurrence after defect closure in laparoscopic ventral hernia repair with a permanent tack fixated mesh: a nationwide cohort study

Abstract: This nationwide cohort study showed a reduced risk of re-operation for recurrence if defect closure was performed in addition to permanent tacks as mesh fixation during laparoscopic incisional hernia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…It should be noted in the above study that the authors used a bridging technique without closing the defect. Baker et al, in a nationwide cohort from Denmark recently showed a reduced risk of reoperation for ventral hernia recurrences if the defect is closed during laparoscopic repair, in addition to the use of permanent tacks [28]. Though not universally recorded in the present study, the use of fascial closure may have contributed to the low recurrence rate to date, along with greater confidence among Club Hernie surgeons to use large pieces of mesh even for mid-sized defects.…”
Section: Discussionmentioning
confidence: 63%
“…It should be noted in the above study that the authors used a bridging technique without closing the defect. Baker et al, in a nationwide cohort from Denmark recently showed a reduced risk of reoperation for ventral hernia recurrences if the defect is closed during laparoscopic repair, in addition to the use of permanent tacks [28]. Though not universally recorded in the present study, the use of fascial closure may have contributed to the low recurrence rate to date, along with greater confidence among Club Hernie surgeons to use large pieces of mesh even for mid-sized defects.…”
Section: Discussionmentioning
confidence: 63%
“…Closure of the defect is becoming more widely advocated nowadays [13][14][15][16][17]. We should mention that we were not closing the defects before applying mesh in the past, and we are closing the defects in selected cases now.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, few modifications have been shown to improve outcomes including primary closure of the hernia defect. 23 Sac removal was also advocated to reduce seroma formation. Beyond technique, focus has been on improving mesh material in an attempt to reduce recurrence rate, complications, and adhesion formation.…”
Section: Discussionmentioning
confidence: 99%